PARTICULAR FEATURES OF OVARIAN CYSTS AND ENDOMETRIOSIS TREATMENT - I. S. Sidorova; A. L. Unanyan (IRBIS LLC, 2016)
One of the commonest forms of genital endometriosis is the ovarian endometriotic lesion. The main treatment step, surgical intervention, may promote endometriosis progression if performed non-radically. Analysis of clinical particulars of disease in two comparison groups. The clinical particulars of disease were studied on 139 patients divided into 2 groups: the first group (41 females) comprised patients with repeated hospitalization due to recurrent endometriotic cysts at the backdrop of conducted anti-relapsing therapy. The second group included 98 patients hospitalized with newly diagnosed endometriotic cyst, and in whom after surgical treatment, there was no recurrence during 2-3 years after surgery. For evaluation of recurrence risk, 10 criteria have been assessed: the immunohistochemical parameters, such as CD-95; Ki-67; CD-34; ММР-7; TIMP-1; EGF; the level of circulation using color Doppler mapping; diagnosed peritoneal endometriosis; presence of microfocal ovarian endometriosis and intensity of clinical manifestations. Should 3 or less signs be present, this was defined as the low rate of risk of recurrence, and in case of 4, 5 or 6 signs present, this was defined as the moderate rate of risk of recurrence. In case of high recurrence rate, the post-operation therapy was conducted using hormonal drugs (GnRh-A for 6 months). In case of moderate rate of risk the administration of a variant of hormonal therapy was decided upon individually. In case of low recurrence rate, the combination oral contraceptives were administered aimed at prophylaxis of recurrence. The results of investigation confirm that studying of individual prognosis of recurrence in patients with ovarian endometriotic cysts is gaining an increasingly greater significance owing to the necessity to draw up a rational plan of differential approach to treatment based on scientifically substantiated prognosis